Report on Events in Hungary October 23 - December 31, 1956. Official Yugoslav Statement Published on the Abduction of Nagy - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Detail of the Abduction: despite the promises given by the Hungarian government that these people will be allowed to return home after leaving their asylum in the Yugoslav Embassy in a bus, Soviet military personnel had entered the Embassy building, and a Lieutenant Colonel of the Soviet Army forced two Yugoslavs (embassy personnel) to leave while the bus, escorted by a Soviet armored car, drove off to an unknown destination. Summary of World Broadcast, Part II. B No. 785, page 53; Summary of a report published by Yugoslav Press Agency.